Loneliness and symptom burden in oncology patients during the COVID‐19 pandemic. Issue 17 (27th April 2021) - Miaskowski, Christine; Paul, Steven M.; Snowberg, Karin; Abbott, Maura; Borno, Hala T.; Chang, Susan M.; Chen, Lee May; Cohen, Bevin; Cooper, Bruce A.; Hammer, Marilyn J.; Kenfield, Stacey A.; Kober, Kord M.; et al.
Abstract : Background: Loneliness and social isolation are significant public health problems that are being exacerbated during the coronavirus disease 2019 pandemic. Little is known about the associations between loneliness and symptom burden in oncology patients before and during the pandemic. Study purposes include determining the prevalence of loneliness in a sample of oncology patients; evaluating for differences in demographic, clinical, and symptom characteristics between lonely and nonlonely patients; and determining which demographic, clinical, and symptom characteristics were associated with membership in the lonely group. Methods: A convenience sample (n = 606) completed online surveys that evaluated the severity of loneliness, social isolation, and common symptoms (ie, anxiety, depression, fatigue, sleep disturbance, cognitive dysfunction, and pain) in oncology patients. Parametric and nonparametric tests were used to evaluate for differences in scores between the lonely and nonlonely groups. Logistic regression analysis was used to determine risk factors for membership in the loneliness group. Results: Of the 606 patients, 53.0% were categorized in the lonely group. The lonely group reported higher levels of social isolation, as well as higher symptom severity scores for all of the symptoms evaluated. In the multivariate model, being unmarried, having higher levels of social isolation, as well as higher levels of anxiety and depressive symptoms were associated with membership in the lonely group. Conclusions: Study findings suggest that a significant number of oncology patients are experiencing loneliness, most likely as a result of mandate social distancing and isolation procedures. The symptom burden of these patients is extremely high and warrants clinical evaluation and interventions. Abstract : Little is known about the experience of loneliness in oncology patients during COVID‐19. Of the 606 patients in this study, 53% report a clinically meaningful level of loneliness. Associations are found between loneliness and higher levels of social isolation, anxiety, and depressive symptoms.